ASUHAN KEBIDANAN PADA IBU HAMIL DENGAN PEMBERIAN SEDUHAN JAHE UNTUK MENGURANGI EMESIS GRAVIDARUM DI PUSKESMAS TANJUNG BALAI KARIMUN - Titin Sartini; Risqi Utami; Nova Roza (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2023)
According to the Indonesian Ministry of Health in Indonesia, 50% -75% of pregnant women experience nausea and vomiting in the first trimester or early in pregnancy. Non-pharmacological therapy to reduce emesis gravidarum can be herbal plants, including ginger. The aim of the study was to provide midwifery care for pregnant women in a comprehensive and sustainable manner for pregnant women with emesis gravidarum through giving ginger infusion. Case reports in this case study use the case study method. The study was carried out at the Tanjung Balai Karimun Health Center in March 2023. The subjects used were pregnant women with emesis gravidarum. Data collection methods are participatory observation, interviews, measurements, documentation. Providing midwifery care to pregnant women by giving ginger infusion to reduce emesis gravidarum has been carried out using 2.5 grams of white ginger which is thinly sliced ​​and then brewed with 250 ml of hot water plus 10 grams of white sugar. The ginger brew is drunk 2x1 (morning and evening) in warm conditions for 4 days. The results of the study found that the mother felt her nausea and vomiting had decreased since consuming ginger infusion and continued to consume ginger infusion until her nausea and vomiting disappeared